Contribution of game genre and structural game characteristics to the risk of problem gaming and gaming disorder: a systematic review - Rehbein, Florian (Current addiction reports, 2021)
Purpose of Review - With its inclusion in the International Statistical Classification of Diseases and Related Health Problems, 11th Revision, gaming disorder (GD) has been officially recognized as a behavioral addiction. Etiological models of GD refer to the interaction of personal, environmental, and game-related risk factors. However, the role of video game characteristics in the development of problem gaming and GD is not well understood. This systematic review summarizes the literature that examines the association between video game genres and structural characteristics and GD symptoms. Recent Findings - Recent studies report that playing massively multiplayer online role-playing games, first-person shooters, and real-time strategy games/Multiplayer Online Battle Arena (MOBA) is associated with more time spent gaming and higher endorsement of GD symptoms. Reward and punishment features (reinforcement), social features, and monetization features have been associated with more frequent gaming and higher scores on self-report measures of GD. The literature is limited due to inconsistencies in measurement of game features, as well as other methodological weaknesses, demonstrating the need for higher quality studies, including studies of individuals with verified gaming disorders to understand their use of specific games. Summary - Current research suggests that some game types containing certain structural game characteristics are positively related to problem gaming. We propose that future studies are guided by theory-based taxonomies of structural game characteristics and examine game influences using experimental designs. For this purpose, a measurement tool to aid the investigation of diverse elements of video game characteristics would be valuable.